Evaluation of white Kwao Krua (Pueraria candollei Grah. ex Benth.) products sold in Thailand by molecular, chemical, and microscopic analyses - Aekkhaluck Intharuksa (2020)
© 2019, The Japanese Society of Pharmacognosy. The tuberous roots of Pueraria candollei Grah. ex Benth. (Fabaceae), commonly known as white Kwao Krua, are used to relieve menopausal symptoms in Thai traditional medicine because they contain phytoestrogens. Black and red Kwao Krua crude drugs exist as well, but they have different botanical origins and pharmacological activities. There is a high demand for white Kwao Krua products, but because of the limited availability of the plant material, it is suspected that the adulteration and misidentification of white Kwao Krua crude drugs and products occur. In this study, we authenticated white Kwao Krua products collected from Thai herbal markets by molecular, chemical, and microscopic analyses. The nucleotide sequences in the internal transcribed spacer (ITS) and trnH–psbA regions of 23 samples of authentic P. candollei were analyzed, and both regions were found to have intraspecific DNA polymorphisms. Based on the single nucleotide polymorphisms in the ITS1 region, species-specific primer sets of P. candollei were designed to authenticate white Kwao Krua and differentiate it from red and black Kwao Krua. Only the PCR products of KWP02 were not amplified by the primer sets. Isoflavonoid contents and microscopic features were used to support the results of molecular analysis to clarify the botanical origin of white Kwao Krua. Molecular, chemical and microscopic methods confirmed that all the Thai Kwao Krua products examined in this study contained authentic “white Kwao Krua” as claimed on their labels.